Kinematic Analysis of a 3-DOF Parallel Polishing Manipulator - Bao Xinmian; Wang Xuelei; Zhang Weitao; Wang Lu; Zhao Dongjie (Jixie chuandong)
A 3-DOF parallel manipulator with X, Y movement and Z rotation for the end-effector is studied in order to meet the requirements of copying and polishing of louver blades. In order to verify the kinematic performance of the manipulator, firstly, the mechanism characteristics are described, and the degree of freedom of the mechanism is analyzed based on the spiral theory. Secondly, the kinematics equations of the mechanism are constructed based on the closed-loop vector method, the forward and inverse position solutions are analyzed, and the analysis results are preliminarily verified by concrete examples. Finally, the numerical simulation model and virtual prototype model of the mechanism are constructed, and the inverse kinematics simulation analysis of the position and velocity is carried out. The simulation results show that the analysis results of the two models are consistent, and the result of inverse solution is reliable. The arm chain can coordinate the movement, the movement process is smooth, and the displacement and velocity curves are smooth and without mutation, and can provide a basis for the size optimization and motion control of the manipulator.